2010
DOI: 10.1016/j.juro.2010.08.003
|View full text |Cite
|
Sign up to set email alerts
|

The Learning Curve for Laparoscopic Radical Prostatectomy: An International Multicenter Study

Abstract: Purpose It is not yet possible to estimate the number of cases required for a beginner to become expert in laparoscopic radical prostatectomy. We estimated the learning curve of laparoscopic radical prostatectomy for positive surgical margins compared to a published learning curve for open radical prostatectomy. Materials and Methods We reviewed records from 8,544 consecutive patients with prostate cancer treated laparoscopically by 51 surgeons at 14 academic institutions in Europe and the United States. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
96
1
11

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(117 citation statements)
references
References 16 publications
9
96
1
11
Order By: Relevance
“…Secin et al . [ 13 ] , in their large international multicentre study of 8544 LRP cases, primarily investigating learning curves, reported an overall PSM rate of 22%. The authors highlighted the well-known problem of a prolonged learning curve in LRP, plateauing at ∼ 200 -250 cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secin et al . [ 13 ] , in their large international multicentre study of 8544 LRP cases, primarily investigating learning curves, reported an overall PSM rate of 22%. The authors highlighted the well-known problem of a prolonged learning curve in LRP, plateauing at ∼ 200 -250 cases.…”
Section: Discussionmentioning
confidence: 99%
“…The authors highlighted the well-known problem of a prolonged learning curve in LRP, plateauing at ∼ 200 -250 cases. BCR-free survival rates were not investigated owing to a lack of follow-up data [ 13 ] . Although the authors primarily looked at learning curves, the PSM rate seems fairly low; however, owing to the fact that after 200 cases a plateau was achieved and the overall number of patients included in this study was remarkable, higher PSM rates produced during the learning curve did not negatively impact the overall PSM rate of the entire cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, 1-and 3-month continence outcomes (strict pad-free definition) should have also been reported as earlier recovery has been demonstrated in several reports. 2,6 Interestingly, pT2-PSM rates (22% vs. 17%) appear moderately high when compared to high volume surgeons (4%-16%).…”
mentioning
confidence: 98%
“…Ideally, 1-and 3-month continence outcomes (strict pad-free definition) should have also been reported as earlier recovery has been demonstrated in several reports. 2,6 Interestingly, pT2-PSM rates (22% vs. 17%) appear moderately high when compared to high volume surgeons (4%-16%). 2,7 Similarly, there is a concern for the lymph node yield for both ORP (5.4) and RARP (3.9) groups when compared to contemporary reported series, 8 Robot-assisted radical prostatectomy: Another Canadian experience robot-assisted radical prostatectomy extended pelvic lymph node dissection is recommended.…”
mentioning
confidence: 98%
“…В мульти-центрическом исследовании Secin et al [9] показано, что количество радикальных про-статэктомий, выполненных с «чистым» хи-рургическим краем, постепенно возрастает по мере увеличения личного опыта хирурга, хотя авторы при этом настаивают, что про-фессионализм не есть простое накопление количества произведённых операций. Даже опытный хирург может постоянно повторять одну и ту же интраоперационную техническую ошибку, не улучшая тем самым результаты сво-их оперативных вмешательств.…”
unclassified